2017
DOI: 10.3892/ol.2017.5920
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of immunophenotyping on the prognosis of multiple myeloma patients treated with bortezomib

Abstract: Abstract. In the present study, the effect of immunophenotyping on the prognoses of patients with multiple myeloma (MM) treated with bortezomib plus dexamethasone was investigated. The study involved 46 patients with MM, and analyzed the prognostic significance of the expression of cluster of differentiation (CD)45, CD56 and mature plasma cell (MPC)-1, and other factors including the International Staging System (ISS) stage, age, gender, the immunoglobulin subtype and the treatment line number prior to bortezo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The expression of CD45− was associated with shorter survival in our MM patients with EMR in this study. CD45− myeloma cells is reported to be an unfavourable prognostic marker in the high‐dose therapy; however, opposite results are shown in the current studies carried out after the introduction of novel agents . This discrepancy is due to different treatment strategies and setting such as EMR.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The expression of CD45− was associated with shorter survival in our MM patients with EMR in this study. CD45− myeloma cells is reported to be an unfavourable prognostic marker in the high‐dose therapy; however, opposite results are shown in the current studies carried out after the introduction of novel agents . This discrepancy is due to different treatment strategies and setting such as EMR.…”
Section: Discussionmentioning
confidence: 67%
“…CD45− myeloma cells is reported to be an unfavourable prognostic marker in the high-dose therapy 16 ; however, opposite results are shown in the current studies carried out after the introduction of novel agents. 17,18 This discrepancy is due to different treatment strategies and setting such as EMR. The present results showed that CD45 in bone marrow appears to be reliably expressed in EMR specimens.…”
Section: Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The immature type had a higher grade of malignancy that affected prognosis [21]. Thus, newly diagnosed MMs were classified into immature, intermediate, and mature types based on the presence or absence of MPC-1 and the expression of adhesion factors CD45 and CD49e [22][23][24]. The immature type demonstrated a larger nuclear size, narrower cytoplasm, and an increased nucleus-to-cytoplasm (N:C) ratio [25].…”
Section: Patient Cohort and Study Designmentioning
confidence: 99%